The Correlation of Ideology and Utopia - Mikayelyan, Meri (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
For centuries, numerous projects have been raised for the organization and regulation of life which somehow affect human’s perception of the world and his position in life. The attempts to comprehend the social reality are always mixed with ideas on what it should be. And from here derives continuous highlighted utopias and ideologies uninterrupted parade. In the article, similarities and differences of utopia and ideology, as well their place and role in the social life have been considered. Simultaneously, utopia and ideology both prevent and assist the human and society in orientating through becoming a landmark in the social and political life.